Levels Of Conjugated Linoleic Acids In Kedah-Kelantan Cattle And The Cytotoxic Effects Of Selected Conjugated Linoleic Acid Isomers On Cancer Cell Lines - Beyene, Achenef Melaku (2009)

(untitled)
Conjugated linoleic acids (CLAs) are group of positional and geometric isomers of octadecadienoic acid (18:2) with conjugated double bonds and believed to have many health promoting effects. The present study focused on determination of the levels of CLAs in liver, superficial pectoral, longissimus dorsi, semimembranosus muscles and rumen liquor of Kedah-Kelantan (KK) cattle and assessment of the cytotoxic effects of selected conjugated linoleic acid (CLA) isomers on human breast (MCF7), liver (HepG2) and colon (HT-29) cancer cell lines. One hundred and ten samples were collected from Banting and Kuantan abattoirs, Malaysia from May to June 2007 for the measurement of CLAs levels. Fatty acids were extracted using modified Folch’s method and their profile was determined by gas chromatography. The average contents of CLAs in the liver, superficial pectoral, longissimus dorsi and semimembranosus muscles were 38.71 ±15.27, 18.24 ±10.12, 11.03 ±5.96 and 13.04 ±5.56 mg/100g of sample, respectively. The average amount of CLAs in rumen liquor was 15.00 ±17.04 mg/100mL of sample. The quantity of CLAs in the liver was significantly (P < 0.05) higher than other samples. There was no significant difference among muscles in mg/100g CLAs but with reference to percentage of fatty acids, superficial pectoral muscle had significantly (P < 0.05) higher proportion of CLAs compared to other muscles. There were no significant differences in the levels of CLAs either between sexes or abattoirs. Neither age nor carcass weight was significantly correlated with the levels of CLAs. The percentages of cis-9, trans-11 (c9,t11) CLA isomer were 63.39 ±23.16, 90.66 ±20.47, 82.82 ±14.83, 76.04 ±21.98 and 55.20 ±16.87 % of total CLAs in the liver, longissimus dorsi, semimembranosus, superficial pectoral muscles and rumen liquor, respectively. The proportions of trans-10, cis-12 (t10,c12) CLA isomer were 20.77 ±14.44, 21.00 ±18.64, 10.43 ±16.43, 7.62 ±13.43 and 18.60 ±15.61 % of the total CLAs in liver, superficial pectoral, semimembranosus, longissimus dorsi muscles and rumen liquor, respectively. Positive correlations between CLAs and trans (t)11-octadecenoic (18:1) acid concentration were observed in liver (r = 0.556, P < 0.05), superficial pectoral (r = 0.642, P < 0.05), semimembranosus (r = 0.520, P < 0.05), longissimus dorsi (r = 0.489, P < 0.05) muscles and rumen liquor (r = 0.538, P < 0.05). Significant positive correlations were also observed between CLAs and octadecanoic (18:0) acid (r = 0.572, P < 0.05), CLAs and c9,c12-octadecadienoic (linoleic) (18:2) acid (r = 0.551, P < 0.05) and CLAs and octadecatrienoic (18:3) acid (r = 0.523, P < 0.05) in rumen liquor. Rumen pH was positively correlated with c9,t11 CLA isomer but negatively correlated with t10,c12 CLA isomer. For cytotoxicity studies, MCF7, HepG2 and HT-29 cancer cell lines were grown on RPMI 1640 media and treated with different concentrations of c9,t11; t10,c12 and mixed isomers CLA for 72 hours. The results were determined by microculture tetrazolium (MTT) cytotoxicity assay, acridine orange/propidium iodide (AO/PI) staining and terminal uridyltransferase nick end labelling (TUNEL) assay. From MTT assay, it was found that the viability of MCF7, HepG2 and HT-29 cancer cell lines had been reduced significantly (P < 0.05) by all CLA isomers used in a dose-dependent manner. The median inhibitory concentration (IC50) value was varied not only with type of CLA isomer but also with cancer cell lines. t10,c12 CLA isomer showed the strongest cytotoxic effect on the MCF7 cancer cell lines whereas the mixed isomers on HepG2 and HT-29 cancer cell lines. c9,t11 CLA isomer was the least potent in all cell lines tested. From the AO/PI staining, cell shrinkage, and membrane ruffling and blebbing were observed in treated MCF7 and HepG2 cells. It was observed by the TUNEL assay that all CLA isomers significantly (P < 0.05) induced higher proportion of apoptosis in MCF7 and HepG2 cell lines. It was also observed that the treated HepG2 and MCF7 cells showed a significantly (P < 0.05) higher proportion of cells in G0/1 but lower proportion in the G2/M phase than the untreated cells. Hence, CLA isomers induced G0/1 arrest in these cell lines. In summary, CLAs are group of fatty acids present in KK cattle meat, which inhibit cancer cell proliferation and viability through cell cycle arrest and induction of apoptosis. The present results warrant future studies particularly in the use of CLAs as chemopreventive and/or chemotherapeutic agents.